Rhabdomyolysis in a Hospitalized 16-Year-Old Boy: A Rarely Reported Underlying Cause - Rishika Singh; Dilip R. Patel; Sherry Pejka (Case Reports in Pediatrics)
Rhabdomyolysis can occur because of multiple causes and account for 7% of all cases of acute kidney injury annually in the United States. Identification of specific cause can be difficult in many cases where multiple factors could potentially cause rhabdomyolysis. We present a case of 16-year-old male who had seizures and was given levetiracetam that resulted in rhabdomyolysis. This side effect has been rarely reported previously and like in our case diagnosis may be delayed.